Pendampingan Penerapan Kurikulum Cinta sebagai Strategi Pembelajaran Humanis di MTs - Arif Sholehudin; Sayid Umar (PT Cendekia Education Center, 2026)
This community service program aimed to support teachers in implementing the Love Curriculum as a humanistic learning strategy in Islamic secondary education. The program employed a qualitative descriptive approach using participatory mentoring involving 15 teachers from various subject areas. The activities were carried out through three main stages: preparation, mentoring and classroom implementation, and evaluation and reflection. Data were collected through observation, interviews, and documentation, and analyzed qualitatively. The results indicate an improvement in teachers’ understanding of humanistic learning principles and the integration of values such as empathy, compassion, and respect into lesson planning and instructional practices. Teachers demonstrated positive changes in classroom interaction, learning strategies, and their role as facilitators of student-centered learning. The implementation of the Love Curriculum also contributed to the creation of a more inclusive, supportive, and comfortable learning environment that encouraged active student participation. Overall, the mentoring program positively impacted teachers’ pedagogical competence and strengthened the quality of humanistic learning. This program highlights the effectiveness of mentoring-based implementation of the Love Curriculum in fostering humanistic education. Keywords: Love Curriculum, humanistic learning, teacher mentoring, Islamic secondary school, community service.